EFEKTIFITAS PERGUB BALI NO 46 TAHUN 2020 DALAM UPAYA PENANGGULANGAN COVID 19 DI BALI - Putu Ary Prasetya Ningrum (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
The rise of the spread of covid 19 has made many countermeasures carried out, both with regulations and policies carried out by the government for the community, many policies have been carried out to overcome its spread. The soaring cases of Covid 19 in Bali have made the government carry out even harsher policies with sanctions for the community and aiming at community discipline itself. So the issuance of the Governor of Bali Regulation No.46 of 2020 which contains sanctions for people who do not wear masks as a condition of health protocol.